Community Service on Women in the Agricultural Sector in the Langga La'a Farmers Group, Bhera Village, Mego District, Sikka Regency. (International Forum of Researchers and Lecturers, 2025)
Community Service Activity (PKM) Gender and Agricultural Development in the Langga La'a Farmer Group, Bhera Village, Mego District is one of the course programs in the agribusiness study program, especially the extension interest. The purpose of this activity is to increase the capacity of women's self-confidence in taking leadership roles in the agricultural sector at the community, farmer group, or agricultural institution level. In this activity, the method used is to conduct socialization to the Langga La'a Farmer Group, Bhera Village, Mego District, with the theme of Women's Leadership in the Agricultural Sector. The results of this socialization activity can be seen that women also have a very important role in leadership, especially in the agricultural sector, which has often been dominated by men. Therefore, it can be concluded that the community service program from Agribusiness Students of Nusa Nipa University can have a positive impact on the Langga La'a Farmer Group community regarding increasing understanding and awareness of farmer groups regarding the importance of inclusive leadership, as well as opening up space for women to play a role as leaders in the agricultural sector. This community service activity strongly encourages active collaboration between Students and the Langga La'a Farmers Group, this activity not only provides benefits but can also increase public awareness of the importance of the role of women in leadership.